The influence of dioleoylphosphatidylcholine (DOPC) on the lipid sponge phase system - Machingauta, Marshall R.; McEvoy, Aina; Karlsson, Alma; Barauskas, Justas; Nylander, Tommy; Gilbert, Jennifer (Frontiers in Soft Matter, 2025)
The use of lipid nanoparticles (LNPs) in pharmaceutical and food applications has gained momentum due to their capacity to encapsulate a wide range of biomolecules. Previous studies have demonstrated the effective entrapment of enzymes within lipid sponge nanoparticles, highlighting their potential as versatile delivery vehicles. Similar to inverse bicontinuous cubic phases, the sponge phase features a network of aqueous cavities separated by curved lipid bilayers, but with a more flexible structure and larger water cavities. The objective of this study is to determine how the lipid composition affects the sponge phase properties. Based on food-grade lipid mixtures of the glycerol monooleate-rich lipid mixture (GMO-50), diglycerol monooleate (DGMO), polysorbate 80 (P80), and water, which are known to form sponge phases, we have studied the incorporation of the zwitterionic phospholipid 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC). This is of particular interest due to its potential to increase the biocompatibility of the formulation. Using small-angle X-ray scattering (SAXS) and cryogenic transmission electron microscopy (cryoTEM), we show that DOPC generally promotes the formation of lamellar phases at 25 °C, but sponge phases can be preserved by adjusting GMO-50/DOPC ratios, adding P80, or increasing the temperature to 40 °C. Dispersions in excess water yielded mixtures of sponge nanoparticles and vesicles, while diluting the LNPs in buffers with higher ionic strength (PBS and cell medium) induced multilamellar vesicle formation. These results demonstrate that DOPC provides a tunable handle on lipid nanostructures, enabling temperature and medium-responsive systems, and that the surrounding medium can restructure nanoparticles even after formation. This underscores the importance of considering both the conditions of nanoparticle assembly and their response to new environments, with direct implications for biopharmaceutical performance.